Three dimensional stagnation point flow of bionanofluid with variable transport properties - Amirsom, N.A.; Uddin, M.J.; Ismail, A.I. (Elsevier, 2016)
Bionanofluid is a nanofluid in which bioconvection occurs. This paper studies the three dimensional steady stagnation point flow of a bionanofluid with variable transport properties. All the transport properties are dependent on the concentration. Zero mass flux and thermal convective boundary conditions are taken into account. The governing equations of the problem are nondimensionalized and transformed into a set of similarity equations using similarity transformation generated by Lie group analysis. The transformed equations are solved numerically using the Runge-Kutta-Fehlberg fourth-fifth order numerical method (RKF45). The solutions depend on the viscosity parameter, thermal conductive parameter, mass diffusivity parameter, microorganism diffusivity parameter, Schmidt number, bioconvection Schmidt number and Pe´ clet number. These controlling parameters affect the dimensionless velocity, temperature, nanoparticle volume fraction, microorganisms, the skin friction coefficient, the local Nusselt number and the Sherwood number as well as the motile microorganism rate and are displayed graphically. The results were found to be in good agreement with previous related studies.